Secret Yosemite : [videorecording (DVD)] : explore beyond the tourist hotspots (Warner Home Video, 2007)
Experience a day in one of America's greatest parks, Yosemite National Park in California. Home to over 2000 plant and animal species, steep granite cliffs, and the world's largest trees- the Sequoias. View where 3.5 million visitors come every year.